MEMBINA PENGHARAPAN UMAT KATOLIK DI TENGAH PANDEMI - Vincentius Yossy Kareli; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Bahasa Indonesia, 2022)
The discussion of the Church's Hope on Eternal Life is a very interesting topic to explore during this pandemic situation which has taken many lives every second. This theme is very close to human life. The problem to be discussed into this research is, to begin with about how Catholics are in their faith relationship. Furthermore, is about how Christians embrace the COVID-19 pandemic situation and involves other people around them doing the same. For eternal life which has been for them since baptism is not a promise in vain. It takes effort and cares to grow it all. These problems were discussed using qualitative research methods with respondents who came from various backgrounds of age, occupation, place of residence, and status of their involvement in church life. The finding of this study is that Catholics manifest their faith by doing positive activities that involve others such as sharing positive experiences, struggles, and strengthening spiritual life. In addition, to embrace this pandemic, Catholics raise awareness of Christian solidarity, because for a member of the Church, faith must not be individualistic. To sum up, Spe Salvi's encyclical helps people open and lift themselves from the trap of despair and stand firm of their faith. Thus contemplation of actions and contemplated actions becomes a powerful weapon to spread Catholicism during this pandemic.